2013
DOI: 10.1007/s11940-013-0274-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in Stroke Patients

Abstract: Patients with severe ischemic and hemorrhagic stroke may require tracheostomy in the course of their disease. This may apply to stroke unit patients whose deficits include a severe dysphagia posing such risk of aspiration as it cannot be sufficiently counteracted by tube feeding and swallowing therapy alone. More often, however, tracheostomy is performed in stroke patients so severely afflicted that they require intensive care unit treatment and mechanical ventilation. In these, long-term ventilation and prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 78 publications
2
30
0
1
Order By: Relevance
“…A tracheotomy is one of the most common surgical procedures on the intensive care unit (ICU) and is reported to be performed in 10-15 % of cases in mixed patient collectives [15]. In stroke patients treated on the ICU a tracheotomy seems to be performed even more frequently with numbers ranging from 15 to 35 % [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A tracheotomy is one of the most common surgical procedures on the intensive care unit (ICU) and is reported to be performed in 10-15 % of cases in mixed patient collectives [15]. In stroke patients treated on the ICU a tracheotomy seems to be performed even more frequently with numbers ranging from 15 to 35 % [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In stroke patients treated on the ICU a tracheotomy seems to be performed even more frequently with numbers ranging from 15 to 35 % [16,17]. Typical indications for a tracheotomy in general critical care are long-term ventilation due to prolonged respiratory failure, need for airway protection because of dysphagia with an increased aspiration risk, functional/ mechanical obstruction, or prolonged need for endotracheal suctioning of secretions [15]. Although there is still some debate surrounding this topic, today a tracheotomy in ventilated ICU patients is supposed to prevent laryngeal and tracheal damage, to shorten the duration of mechanical ventilation, to reduce the length of stay on the ICU, and to cut down the related hospital costs [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with post-stroke dysphagia have a three-times higher risk to develop pneumonia; if aspiration can be detected, the risk rises up to 11.5-times higher [4]. 1.3 – 7.1% of all stroke patients are tracheotomized [8, 9] due to severe dysphagia with prolonged insufficient airway protection or the need for long-term ventilation [10]. The tracheostomy rate of stroke patients on the intensive care unit (ICU) is even higher and ranges between 14 – 35%, exceeding the tracheostomy rates of mixed ICU patient collectives which lie at 10 – 15% [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Another small study that included only middle cerebral artery infarcts suggested that laterality might be associated with extubation success, with left hemisphere AIS having considerably better outcome 5 . However, there are no well-defined clinical tools to guide extubation practices in AIS patients 6 .…”
Section: Introductionmentioning
confidence: 99%